Progressive collapse behaviour of reinforced concrete flat slab buildings subject to column failures in different storeys - Garg, Suyash; Agrawal, Vinay; Nagar, Ravindra (Materials today : proceedings, 2021)
The progressive collapse of buildings could result in significant financial losses and casualties, and it is therefore of the utmost importance to reduce the risks of such occurrences. Flat-slab buildings are much more prone to progressive collapse than moment-frame buildings, since as there are no beams for redistributing the loads that the lost column initially resisted. Even more consideration should, therefore, be given to assessing the progressive collapse of flat-slab buildings. The current analytical research assesses the progressive collapse behaviour of eight-storey R.C flat slab building, with and without perimeter beams, by conducting linear static progressive collapse analysis as per the GSA guidelines (2016). This research explores the column removal situations for various typical positions on each storey, unlike earlier studies where only certain typical columns on the first storey are removed. The results are analyzed for each scenario in terms of joint vertical displacement and chord rotation at column removal locations, and thus the susceptibility of the building to progressive collapse is calculated in compliance with the relevant accepted criteria laid down in the DoD Guidelines (2009). The results showed that the incorporation of perimeter beams in flat slab buildings improved the progressive collapse resistance as it reduces joint displacement and chord rotation at column removal locations by providing sufficient stiffness and load paths for increased gravity loads.